Principal's Academic Supervision Strategy Based on Coaching Techniques to Improve Teacher Teaching Quality - Khawadits, Khawadits; Diat Prasojo, Lantip (Journal of Educational Sciences, 2025)
This study aims to explore the academic supervision strategies implemented by school principals to improve the teaching quality of teachers at SMP Negeri Kecamatan Siak, focusing on three main aspects: planning strategy, implementation strategy, and evaluation and follow-up strategy of academic supervision. Using a qualitative approach with a phenomenological method, this study involved in-depth interviews, observations, and document analysis at SMPN 2 and SMPN 4 Siak from August to October 2025. The results showed that the academic supervision carried out by the principals in SMP Negeri Kecamatan Siak emphasized professional development of teachers rather than just administrative evaluation. In the planning stage, principals involved teachers from the outset to build mutual understanding. During the implementation phase, different challenges were found in each school: at SMPN 2, psychological barriers emerged as some teachers felt awkward and tense during the supervision process, limiting openness to feedback, while at SMPN 4, administrative barriers occurred due to the focus of supervision being more on checking teaching materials rather than substantive pedagogical support. However, SMPN 4 had implemented an effective monitoring and follow-up system, although the adoption of positive practices had not yet been widespread among teachers.